A Correlational-Comparative Study of Grade 3 and Grade 4 Students’ Self-Efficacy for and Enjoyment of Learning Mathematics at a Catholic School in Bangkok, Thailand - Techavichian, Supaporn; Lynch, Richard (Scholar: Human Sciences, 2021)
This study aimed to investigate the levels of Grade 3 and Grade 4 students’ self-efficacy for and enjoyment of learning mathematics and to determine whether there was a significant difference or a significant relationship among them at a Catholic school in Bangkok, Thailand. The study was conducted with 46 Grade 3 students and 51 Grade 4 students in the 2019 academic year. The research design was a quantitative correlational-comparative study. The research instrument utilized was the Self-Efficacy for and Enjoyment of Learning Mathematics Questionnaire (SEELMQ), adapted from the Math and Me Survey (Adelson & McCoach, 2011). Descriptive statistics, dependent samples t-tests, independent samples t-tests, and Pearson’s correlation coefficient analysis were used to analyze the data. The findings revealed no significant difference between Grade 3 and Grade 4 students’ self-efficacy for and enjoyment of learning mathematics, but there was a significant difference between students’ self-efficacy for and enjoyment of learning mathematics within their Grade level. Students’ self-efficacy was in a moderate level and students’ enjoyment was in a high level. Moreover, the study revealed a positive strong relationship between students’ self-efficacy for and enjoyment of learning mathematics. Recommendations for school administrators, mathematics teachers, students, parents, and future researchers were provided.